The Frontier Myth in U.S. Offshore Wind Energy Communication - Hernandez, Nicolas C.; Horton, Cristi C.; Endres, Danielle; Peterson, Tarla Rai (Frontiers in Communication, 2019)
Increased penetration of low-carbon energy technologies into the U.S. energy system has the potential to reduce greenhouse gas emissions, facilitate transmission of energy to remote regions, and increase opportunities for public participation in energy system change. It also offers a window of opportunity to observe the social dynamics of rapid system change. Studying internal, yet informal, communication among energy professionals enables communication researchers to probe processes and practices of identity composition, which may, in turn, suggest opportunities to shift the relationship between energy professionals and energy consumers away from alienation and toward consubstantiation. With this goal in mind, we analysed communication among U.S. offshore wind professionals at professional conferences. Textual analysis of conference presentations and ethnographic interviews indicates that the nascent U.S. offshore wind industry is composing an identity inspired by the frontier myth. We suggest that these evocations of frontier imagery could be strategically used to cultivate consubstantiality between technically oriented energy professionals and lay publics. Awareness of a common connection to frontier mythology may contribute to public affinity and engagement with offshore wind energy specifically, and more generally, with low-carbon energy technologies.